Room-temperature fabrication of superhydrophobic covalent organic framework (COF) decorated cotton fabric for high-flux water-in-oil emulsion separation. Issue 87 (18th October 2021) - Chen, Li; Zhou, Cailong; Yang, Hao; Lin, Jia; Ge, Yu; Zhou, Wei; Lu, Chenyang; Tan, Luxi; Dong, Lichun
Abstract : We report the preparation of a two-dimensional superhydrophobic covalent organic framework (COF)-coated cotton fabric via a rapid one-step method at room temperature. Abstract : We report the preparation of a two-dimensional superhydrophobic covalent organic framework (COF)-coated cotton fabric via a rapid one-step method at room temperature. The COF-coated fabric was found to have stable superhydrophobicity and remarkable water-in-oil emulsion separation capacity with ultra-high flux under only gravity.